High temperature operation In(Ga)As quantum dot infrared photodetector focal plane arrays passivated with 6.5 nm-thick Al 2 O 3 layer. (17th March 2014) - Tang, Shiang-Feng; Lin, Wen-Jen; Chen, Tzu-Chiang; Lin, Shih-Yen
Quantum dot infrared photodetectors (QDIPs) have been shown to be a key technology in broad infrared wavelength (3–12 µm) detection due to their potential for normal incidence operation, low dark current density and higher temperature operation. In our research, we have been investigating infrared detectors based on intersubband transitions in a novel InAs/In0.15 Ga0.85 As quantum dots-in-well (DWELL) and normal GaAs-capped InAs quantum dot heterostructures. The study is to demonstrate a dual-band infrared image based on two stacked InGaAs and GaAs- capped InAs QDIP structure, with the use of nano-scale Al2 O3 surface passivated layer by atomic layer deposition (ALD) system deposited to decrease the device shot noise and boost the operation temperature of the thermal imaging FPA to 180 K. It is worth to mention the specific detectivities (D*) of test device passivated with Al2 O3 measured under 80 K and Vb = –3.3 V for mid-wavelength detection is as high as 2.1 × 10 11 cmHz 1/2 /W. By a two-step selective backside etching process, the uncorrected non-uniformity of NEDT is lowered to 6.7%. It reveals the high uniformity of infrared image taken from QWIP FPA with this proposed process is comparable to the conventional one with the mixture of wet- and dry-etching ICP-RIE.